Pengaruh Aglomerasi, Jumlah Penduduk, Dana Perimbangan, dan Belanja Pemerintah terhadap Ketimpangan antar Wilayah di Provinsi Sumatera Selatan Tahun 2018-2022 - Tessa Jessy Anggriani Nababan; Mulyo Hendarto Robertus (Universitas Diponegoro, 2024)
This research aims to analyze the effects of agglomeration, population size, equalization funds, and government spending on regional disparities in South Sumatra Province from 2018 to 2022. This study employs panel data regression analysis using the Random Effect Model (REM) approach to examine the effect of Agglomeration, Population Size, Equalization Funds, and Government Spending on Regional Disparities in South Sumatra Province from 2018 to 2022. The regression results using the Random Effect Model (REM) with the Generalized Least Squares (GLS) method indicate that, partially, the agglomeration variable has a positive and significant effect on regional disparities in South Sumatra Province. Meanwhile, the population size variable has a negative and significant effect on regional disparities in South Sumatra Province, while equalization funds and government spending do not have a significant impact on regional disparities.